Aprire il dibattito sui commons rurali di montagna nelle regioni alpine in cambiamento. Uno studio esplorativo in Trentino, Italia - Cristina Dalla Torre; Elisa Ravazzoli; Andrea Omizzolo; Alessandro Gretter; Andrea Membretti (Revue de Géographie Alpine)
Most of rural resources in the Italian mountain territories, such as forests, pastures, huts, mountain paths, have historically been governed through collective organizations and institutions that have guaranteed the balance between productive activities and environmental protection. These systems can be framed according to the literature on commons. Although the model of collective resource management is still strongly rooted in the Alpine region, socioeconomic changes underway call into question the way resources are conceived, used and managed by communities and the very concept of community as a reference for a collective resource. Few studies have focused on the transformation and adaptation of commons to the changes taking place, such as the progressive penetration of global economic and demographic megatrends at the local level, with the aim of decoding the new tension between community needs and societal needs. By referring to the concepts of resilience and transformability of social-ecological systems, this paper aims to reflect on the impact of the socioeconomic transformations underway in mountain rural regions, to search for new approaches for the conceptualization of commons and to investigate how commons can be transformed in order to make them resilient and more socially inclusive. For that, an extensive literature review and an exploratory fieldwork using a case study approach have been performed. The paper´s results are exploratory, from which working hypotheses have been derived to be explored in further studies. These hypotheses relate to socio-economic and cultural practices as well as approaches that would enable the re-embedding of the commons in the economy and society undergoing change.